Comparativo de dos técnicas de siembra y dos niveles de fertilización con guano de las islas en precocidad y rendimiento de Allium sativum L. var. Serrano en Santiago de Chuco, La Libertad - Arroyo Esquivel, Segundo Teófilo (2018)
The present investigation was carried out in La Colpa, District and Province of Santiago de Chuco, La Libertad region, at 3115 m.s. in altitude; The objective of this study was to compare the effect of two sowing techniques and two levels of guano fertilization of the islands on early and yield of Allium sativum L. var. Serrano in Santiago de Chuco, La Libertad. The experimental design of randomized complete blocks (DBCA) was used with four treatments and three repetitions. The separation of treatment means was performed using the Tukey test at the 5% level. The treatments were traditional sowing without fertilization (to); traditional sowing with fertilization of 850 kg ha-1 of guano of the islands (t1); sowing of garlic soaked for three days and peeled without fertilization (t2) and sowing of garlic soaked for three days and peeled with fertilization of 850 kg ha-1 of guano from the islands (t3). It is concluded that the technique of sowing with garlic soaked for three days, peeled and with the guano fertilization of the islands of 850 kg ha-1 (t3) obtained the highest average yield, achieving 11.65 kg / 16 m2, the highest average weight of bulb 53.84 gr / per bulb, the highest plant height and the highest precocity in relation to the other treatments, no statistically significant difference being found in the number of teeth per bulb and the number of leaves per plant.